Pola Asuh Orang Tua Terhadap Sosial-Emosional Anak: Studi Deskriptif Di TK Al Ikram Moncongloe - Bunga Norma; Ashar Ashar; Riskal Fitri (Ihya Ulum: Early Childhood Education Journal, 2025)
The socio-emotional aspect is a primary determinant of early childhood's adaptability and long-term academic success. This study aims to comprehensively describe the implementation of parenting styles and their impact on the socio-emotional development profile of children aged 5–6 years at TK Al Ikram Moncongloe, Maros Regency. This location was selected purposively as it represents a sociological transition area from traditional values to a digital lifestyle (suburban). Employing a descriptive qualitative approach, data were collected through moderate participant observation, in-depth interviews with parents and teachers, and documentation studies. The results indicated that parenting styles in this area are concentrated in two dominant poles: authoritative/democratic (55%) and permissive (30%), with a residue of authoritarian parenting (15%). Authoritative parenting is proven to be the best catalyst for shaping stable emotional regulation and strong prosocial independence in children. Conversely, digital-permissive parenting, characterized by the provision of gadgets as a digital pacifier, negatively correlates with children's self-control, thereby triggering focus distortion and low collaborative abilities in the classroom. Meanwhile, authoritarian parenting triggers reactive aggression or extreme passivity due to repressive control. The novelty of this research reveals that in suburban areas, parents' digital literacy becomes a crucial variable in parenting. The implications of the study emphasize the urgency of harmonization between teacher guidance and authoritative parenting at home through structured educational parenting programs.